(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This paper argues that Offred’s survival isn’t just psychological—it’s a technological intervention. By combining the upcoming literary theories of Xenofeminism and Metamodernism, it proves that she uses her own alienation as an ’interface’ to sabotage the state. While Gilead tries to render her as a biological machine, she responds by becoming a ’Glitch’—maintaining a sovereign, encrypted self through the linguistic play and the emotional oscillation. Ultimately, the ’Historical Notes’ prove that she successfully transcended her biological cage to become autonomous data.